2014
DOI: 10.1002/ece3.1143
|View full text |Cite
|
Sign up to set email alerts
|

Ecological divergence and evolutionary transition of resprouting types inBanksia attenuata

Abstract: Resprouting is a key functional trait that allows plants to survive diverse disturbances. The fitness benefits associated with resprouting include a rapid return to adult growth, early flowering, and setting seed. The resprouting responses observed following fire are varied, as are the ecological outcomes. Understanding the ecological divergence and evolutionary pathways of different resprouting types and how the environment and genetics interact to drive such morphological evolution represents an important, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…In forest ecosystems Eucalyptus and some have limited capacity for resprouting and are considered post-fire obligate seeders [14,15]. There are other trees with post-fire epicormic resprouting in Australia as well as in South Africa (Table 1), including examples that exhibit within-species (amongpopulation) variability in epicormic and basal resprouting [16,17].…”
Section: Glossarymentioning
confidence: 99%
“…In forest ecosystems Eucalyptus and some have limited capacity for resprouting and are considered post-fire obligate seeders [14,15]. There are other trees with post-fire epicormic resprouting in Australia as well as in South Africa (Table 1), including examples that exhibit within-species (amongpopulation) variability in epicormic and basal resprouting [16,17].…”
Section: Glossarymentioning
confidence: 99%
“…Cereals are the best example, with a longer domestication time. Throughout domestication, cereals have lost their capacity of seed dispersal and modified their plant architecture in order to increase yield and production (Gepts & Papa 2003, Pickersgill 2007, 2013, Mondolot et al 2008, Chacón-Sánchez 2009, Bautista-Lozada et al 2012, He 2014, but selection of specific traits has reduced the genetic diversity of the domesticated varieties (Chacón-Sánchez 2009, Rauf et al 2010, Bautista-Lozada et al 2012.…”
mentioning
confidence: 99%
“…Previous work has shown that Banksia attenuata has two distinctive growth forms: a tree form that resprouts epicormically, post‐fire, and a shrub form that resprouts from a lignotuber. The two growth forms display consistent morphological differences, and there are no records of the co‐occurrence of both forms within a population (Taylor and Hopper ; He ; Figure ). The morphological divergence patterns between tree and shrub populations show significant concordance with the divergence of neutral genetic markers, and the genetic populations are clustered into two groups (tree and shrub populations), with a minor genetic differentiation between the groups of F ST = 0.27 (He ).…”
Section: Introductionmentioning
confidence: 99%
“…The two growth forms display consistent morphological differences, and there are no records of the co‐occurrence of both forms within a population (Taylor and Hopper ; He ; Figure ). The morphological divergence patterns between tree and shrub populations show significant concordance with the divergence of neutral genetic markers, and the genetic populations are clustered into two groups (tree and shrub populations), with a minor genetic differentiation between the groups of F ST = 0.27 (He ). Despite the striking morphological divergence and absence of cross‐pollination studies between the groups, its taxonomic status as one species has been accepted without dispute (Taylor and Hopper ; Mast and Thiele ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation